A multi-function neonatal incubator for low-income countries: Implementation and ab initio social impact. (March 2020) - Tiam Kapen, Pascalin; Youssoufa, Mohamadou; Foutse, Momo; Dongmeza Koudjou, Jauspin; Mkankam Kamga, François de Paul
Highlights: A multi-function neonatal incubator with remote monitoring, fingerprint scanner, phototherapy, and heart rate monitoring is proposed. Proportional integral (PI) control algorithm and an Android application were developed. An initial social impact of the implemented neonatal incubator usage was performed in some hospitals in Cameroon. Abstract: The World health Organization estimates that about 8 million babies die prematurely worldwide. Most of these cases are found in low-income countries (LICs). The use of neonatal incubators has proven to be very useful in the reduction of infant mortality. However, access to this important medical device is not always easy in LICs. This article presents the implementation of a multi-function neonatal incubator with remote monitoring, fingerprint scanner, phototherapy, and heart rate monitoring. In this view, proportional integral (PI) control algorithm and an Android application were developed. Furthermore, an initial social impact of the implemented neonatal incubator usage was performed in some hospitals in Cameroon.